Pyruvate accumulation may contribute to acceleration-induced impairment of physical and cognitive abilities: an experimental study. Issue 4 (30th April 2021) - Mo, Fengfeng; Zhang, Hongwei; Tang, Yuxiao; Qi, Ruirui; Nie, Shuang; Shen, Hui; Li, Min
Abstract: Background: Fatigue can be induced after acceleration exposure, however its mechanism is still unclear. The aim of the present study was to examine whether metabolites' changes can decrease cognitive and physical function after acceleration. Methods: Graybiel scale and Fatigue Self-rating scale were used to assess the seasickness and fatigue degrees of 87 male seafarers respectively after sailing. To test the effect of pyruvate on cognitive and physical functions, five different doses of pyruvate were administrated into rats. Insulin can reduce the accumulation of pyruvate. To observe the insulin effect on pyruvate, cognitive and physical functions after acceleration, insulin administration or treatment of promoting insulin secretion was used. Physical and cognitive functions were assessed using open field test (OFT), morris water maze (MWM) and loaded swimming test (LST) in animals. Results: Physical and cognitive abilities were decreased obviously, and serum pyruvate increased mostly in human and rats after acceleration. Compared with vehicle group, physical and cognitive abilities were significantly decreased after pyruvate administration. Besides, we found a significant decline in adenosine triphosphate (ATP) concentration and pyruvate dehydrogenase (PDH) activity in the hippocampus, prefrontal cortex, liver, and muscle of rats treated with acceleration or pyruvate injection, while insulin administration or treatment of promoting insulin secretion markedly alleviated this decline and the impairment of physical and cognitive abilities, compared with the control group. Conclusion: Our results indicate that pyruvate has a negative effect on physical and cognitive abilities after acceleration. Insulin can inhibit pyruvate accumulation and cognitive and physical function after acceleration exposure.